Improving pupils’ achievement in fraction using inquiry-based instructional strategy enriched with origami activities (2022)
This study determined the effects of inquiry-based instructional strategy enriched with origami activities and the moderating effect of gender on pupils’ achievement in fraction in Oyo State, Nigeria. The study adopted the pretest-posttest control group quasi-experimental design using a 2x2 factorial matrix. The sample group consisted of 55 boys and 33 girls from two randomly selected public primary schools. Two intact classes were randomly assigned to experimental and control groups. The instruments used were pupils’ achievement test in fraction and teachers’ instructional guides. Data were analysed using analysis of covariance, as well as estimated marginal mean. Treatment had a significant main effect on pupils’ achievement in fraction and there was no significant main effect on gender. Treatment and gender had no significant interaction effect on pupils’ achievement. It was recommended that mathematics teacher should adopt inquiry-based instructional strategy enriched with origami activities.